City of women - Gillham, David R. (New York : G.P. Putnam's Sons, 2012)
Hiding her clandestine activities behind the persona of a model Nazi soldier's wife at the height of World War II, Sigrid Schroeder dreams of her former Jewish lover and risks everything to hide a mother and two young children who she believes might be her lover's family.
"Amy Einhorn Books.&quot
edited hb 2015-06-16
Keywords: Military spouses -- Fiction; Nazis -- Fiction; Women -- Germany -- Berlin -- Fiction; Berlin (Germany) -- History -- 1918-1945 -- Fiction; Historical fiction